2006
DOI: 10.5688/aj700228
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of an Educational Partnership Between Community Pharmacists and Consumer Educators in Mental Health Care

Abstract: Objective. To design and implement an interactive education program to improve the skill and confidence of community pharmacists in providing pharmaceutical services to people with mental illnesses. Design. A literature review was conducted and key stakeholders were consulted to design a partnership that involved community pharmacists and consumer educators. The partnership was designed so that all participants shared equal status. This facilitated mutual recognition of each others' skills. Assessment. Four 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…12,17 In pharmacy, a limited body of research highlights the benefit of training programs for reducing social distance and improving attitudes about mental illness, which, in turn, increases counseling frequency and enhances the quality of care provided to patients living with mental illness. [19][20][21][22][23][24][25] Pharmacy students report higher levels of stigmatization than pharmacists regarding schizophrenia. 24,26,27 Because pharmacy students are the next generation of pharmacists, it is important to examine their perceptions regarding stigma towards patients with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…12,17 In pharmacy, a limited body of research highlights the benefit of training programs for reducing social distance and improving attitudes about mental illness, which, in turn, increases counseling frequency and enhances the quality of care provided to patients living with mental illness. [19][20][21][22][23][24][25] Pharmacy students report higher levels of stigmatization than pharmacists regarding schizophrenia. 24,26,27 Because pharmacy students are the next generation of pharmacists, it is important to examine their perceptions regarding stigma towards patients with mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…24 A study demonstrating the potential value of consumer educators in the education of community pharmacists stated that use of consumer educators should be considered as a strategy for improving the confidence and communication skills of community pharmacists in providing pharmaceutical care for people with mental illnesses such as depression. 23,25 Meanwhile, several studies demonstrated that using consumer educators for pharmacy students reduced mental health stigma, 17,26 improved attitudes, and increased students' self-reported sense of empathy toward people with schizophrenia and depression, even on a long-term basis. 22 However, these studies have reported the impact of consumer educators only in undergraduate training.…”
Section: Introductionmentioning
confidence: 99%
“…21 A consumer educator in mental health care is defined in the literature as a person who has previously received mental health care and works, often on a voluntary basis, to inform and educate professionals, students, and the wider community on mental illness and its effects on individuals, families, and society. 22,23 The use of mental health consumers as educators has been well received in nursing and medical education, especially in Australia. 24 A study demonstrating the potential value of consumer educators in the education of community pharmacists stated that use of consumer educators should be considered as a strategy for improving the confidence and communication skills of community pharmacists in providing pharmaceutical care for people with mental illnesses such as depression.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be due to the life-threatening consequences of asthma exacerbation, and includes ethical debate about the mission of healthcare providers to save lives [25] . Another possible explanation may be the lack of patient involvement, such as expert/standardized patients or consumer educators, in the program [26,27] . Involving the patient in the education program is worth considering as it may affect pharmacists' attitudes toward patient autonomy [28] .…”
Section: Discussionmentioning
confidence: 99%